Cross-Intersection Traffic Analysis: A Case Study of Kyaliwajjala-Namugongo - Lydia Nakiganga (Uganda Christian University, 2024)
This research focused on analyzing traffic congestion at cross-intersections using a case study of Kyaliwajjala-Namugongo junction, Wakiso District-Uganda. The main objective of this study was to optimize traffic flow at the Kyaliwajjala-Namugongo intersection using a geometric design. The study involved carrying out topographic surveys to collect geometric and topographic data and manual traffic counts of the approaches to determine the performance of the intersection. The intersection topography was determined using road profiles generated from the elevation data and Coordinates and performance was assessed from the traffic volumes and traffic flow movements. A geometric design was then recommended at the end of this study to enhance the intersection to cope with the existing and future expected traffic volume. The proposed design is able to cope with the traffic for a design life of 15 years and installation of road signs, clear road markings and construction of raised islands were made to cater for safety of road users.